Determinasi Audit Report Lag pada Perusahaan Sektor Consumer Cyclicals di Bursa Efek Indonesia - Annisa Dwiransa Salsabila; Ahmad Syathiri; Emylia Yuniarti (Owner : Riset dan Jurnal Akuntansi, 2026)
This research investigates the influence of firm operational complexity, auditor specialization, and profitability on the length of audit report lag by focusing on consumer cyclicals sector companies listed on the Indonesia Stock Exchange over the 2021–2024 period. The research population comprises all firms classified under the consumer cyclicals sector that were publicly listed on the Indonesia Stock Exchange throughout the observation period. Samples were selected using a purposive sampling technique based on companies that published complete audited annual financial statements and were not delisted during the research period, resulting in 83 sample companies with a total of 332 observations. This study employs a quantitative approach using secondary data obtained from audited annual financial statements published on the official Indonesia Stock Exchange website. Audit report lag is defined as the time interval, measured in days, between the fiscal year-end and the date on which the audit report is issued. Firm operational complexity is proxied by the natural logarithm of the total number of subsidiaries. Auditor specialization is identified based on the market share held by public accounting firms within the same industry, while profitability is measured using Net Profit Margin. Data analysis is conducted using panel data regression with Random Effect Model approach. The results indicate that firm operational complexity and profitability do not have a significant effect on audit report lag, while auditor specialization has a negative and significant effect. These findings indicate that industry specialized auditors are able to conduct audits more efficiently and reduce audit report lag